Edukasi Dan Pelatihan Message Bayi Pada Ibu Dengan Usia 1-12 Bulan Di Puskesmas Tamalanrea Makassar - M, Warda; Sahabuddin, Sahabuddin; Kereh, Heyni F.; Andriani, Fitri; Rahagia, Rasi; Ekawati, Nur (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Baby massage is slow and gentle stroking movements throughout the baby's body starting from the baby's feet, stomach, chest, face, hands and back. Baby massage is a form of tactile stimulation. Tactile stimuli are the most important in development. The sensation of touch is the most developed sensory at birth. Baby massage stimulation can help the baby's growth and development process, and is part of the bonding process between mother and child. The aim of this community service is to provide training to increase mothers' knowledge and skills in performing baby massage. Participants in this baby massage training are mothers who have babies aged 1 – 12 months who are at the Tamalanrea Health Center. Activities include providing baby massage material, demonstrations, and direct practice of baby massage. Evaluation of increased knowledge is carried out using pre and post tests. The results showed that there was good knowledge of 83.3%, and participants were able to do baby massage well. In conclusion, community service in the form of training increases mothers' knowledge and skills in carrying out baby massage.